Damage Prediction of Monolithic and Non-Monolithic Braced Unreinforced Brick Masonry Walls under Explosion Loadings - Anas S.M.; Al-Dala'Ien R.N.; Alam M.; Umair M. (EDP Sciences, 2024)
Numerous unreinforced masonry (URM) structures worldwide face greater vulnerability to direct threats like earthquakes, wind, impact, or explosions compared to reinforced concrete and steel structures. Given the current worldwide environment characterized by dominance and extremism, the task of safeguarding structures, especially from explosive detonations, presents a growing and crucial obstacle for engineers and researchers. The Masonry Society (TMS) and the Federal Emergency Management Agency (FEMA) have recognized that the primary cause of material damage resulting from explosions is the collapse of walls made of URM. The recent catastrophic explosion at the Beirut seaport in Lebanon, the largest of its kind, serves as a stark reminder to town planners, architects, and structural designers. This tragic incident resulted in an immense loss of building infrastructure overall and specifically affected load-bearing masonry structures, leading to severe injuries and casualties. It underscores the urgent need for comprehensive attention and strategic measures in addressing the vulnerabilities inherent in these structures. This research study explores the response of URM walls, constructed with clay bricks, to out-of-plane blast forces. The walls are braced with either monolithic or non-monolithic transverse walls, and a three-dimensional micro-modeling approach is employed. The analysis is conducted using the Abaqus software, which utilizes the finite element method. Alongside the braced walls, the study also examines a free-standing URM wall without transverse walls. The exposed face of the walls is subjected to peak reflected pressures of 0.38 and 1.01 MPa, generated by explosive charges weighing 4.34 and 7.49 kg-TNT at scaled distances of 2.19 and 1.83 m/kg1/3, respectively. The Concrete Damage Plasticity (CDP) model, which incorporates the influence of strain rate, is utilized to simulate the behavior of masonry under blast loads. Comparisons are made between the computed damage patterns of a wall reinforced with monolithic transverse walls and the experimental results found in existing literature, revealing a notable level of agreement. The influence of both monolithic and non-monolithic joints on the performance of the exposed wall is thoroughly examined and contrasted with one another, as well as with the performance of a free-standing wall. The research indicates that non-monolithic joints between the exposed wall and transverse bracing walls exhibit a greater extent of damage to the bracing walls, as this is predominantly influenced by the response of the exposed wall itself. The Authors, published by EDP Sciences. This is an open access article distributed under the terms of the Creative Commons Attribution License 4.0 (https://creativecommons.org/licenses/by/4.0/).